Review of the National Experience of Measuring Gender Inequality in Ukraine, 2009–2021. Part IІ. Donor’s and Non-governmental Organizations’ Initiatives of Gender Measurements - Skoryk, M. M. (Statistics of Ukraine, 2022)
The second part of the review describes and analyzes national gender measurement practices initiated in Ukraine by international donors and local organizations since 2009. The indisputable focus of international donors (five of the six instruments developed during this period) was found to be local-level measurements. Neither the national nor sectoral dimensions had such interested donor support. Thanks to these developments, certain steps forward have been made: several well-thought-out and well-structured tools have been proposed among the latest and developed by gender specialists from abroad; the thought-over structures of directions of gender measurement are offered. At the same time, all tools developed for the local level: 1) were not correlated and had no connection with previous developments (each of them was developed autonomously); 2) five out of six did not provide a clear link with the national gender measurements, thus creating a gap between the results of local and national gender measurements and making them disproportionate in their results; 3) these tools did not provide, except for the gender passport of the Association of Ukrainian Cities, the regularity of their use, thus continuing the negative trend of irregularity of gender measurements in Ukraine; and did not propose to establish appropriate bodies; 4) did not provide for participation in development teams of relevant research institutions, or even only the participation of academic gender researchers. The developers are definitely dominated by civil society activists and their coordinators from international donor organizations. In addition, the number of developers in such development teams is usually small. This leads to non-compliance with scientific procedures in the development of tools and in the actual measurements and calls into question both the effectiveness of such tools and the objectivity of the results obtained with their help. It also pushes gender issues to the periphery of national research and education practices in Ukraine, depriving the gender equality advocates of the opportunity to integrate gender issues into professional activities in academia. It is because of the exclusion of the academic community from the processes of developing gender measurement tools that Ukraine is unable to obtain such an indispensable source of gender data as research data. Conclusions were made on the serious and diverse experience of Ukraine in the field of national gender measurements, as well as the experience of creating groups and networks of active citizens ready to conduct such measurements to improve the social situation of their communities, regions, and cities. The need to move to the next stage of professionalization of gender measurements, their implementation on a solid professional basis, and integration into the activities of professional statistical, sociological, managerial institutions and communities are pointed out.